1995
DOI: 10.1037/0021-9010.80.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Managing conflict with a subordinate or a superior: Effectiveness of conglomerated behavior.

Abstract: Rather than a single behavior, handling conflict is a conglomeration of behavioral components characterized by a pattern of occurrence and by a pattern of covariation of its components. Theories (R. R. Blake & J. S. Mouton, 1964, 1970; R. E. Walton, 1969) have predicted (a) that the forcing component counters effectiveness and (b) that the problem-solving component enhances effectiveness, especially at a moderate level of occurrence of the forcing component. Systematic observations of videotapes of 116 male po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
0
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(168 citation statements)
references
References 63 publications
5
157
0
6
Order By: Relevance
“…66 Van de Vliert et al (1995) utilizam a expressão "conglomerated conflict behavior" para designar a utilização simultânea ou sequencial de vários graus das diferentes estratégias de gestão de conflitos. determinados aspectos da discórdia, enquanto que competir será mais apropriado para outros aspectos.…”
Section: Estratégias De Gestão De Conflitos E Eficáciaunclassified
“…66 Van de Vliert et al (1995) utilizam a expressão "conglomerated conflict behavior" para designar a utilização simultânea ou sequencial de vários graus das diferentes estratégias de gestão de conflitos. determinados aspectos da discórdia, enquanto que competir será mais apropriado para outros aspectos.…”
Section: Estratégias De Gestão De Conflitos E Eficáciaunclassified
“…Traditionally, research has concluded Figure 13.5 presents the HR managers' perceived conflict management style used by ERs. As mentioned above, ERs tend to combine cooperative and competitive styles (Elgoibar 2013;Euwema and Van Emmerik 2007;Van de Vliert et al 1995). This combination can include a more cooperative or competitive approach and here we appreciate differences between the countries (Munduate et al 1999).…”
Section: Frequency Of Conflicts Between Management and Ersmentioning
confidence: 99%
“…Previous research concluded that ERs tend to combine cooperative and competitive behaviors (Elgoibar 2013;Munduate et al 1999). However, such combinations usually represent either a more cooperative or competitive approach (Van de Vliert et al 1995).…”
Section: Type Of Conflict and Conflict Managementmentioning
confidence: 99%